Regulatory Role of RNA N6-Methyladenosine Modification in Bone Biology and Osteoporosis - Chen, Xuejiao; Hua, Wenfeng; Huang, Xin; Chen, Yuming; Zhang, Junguo; Li, Guowei (Frontiers in Endocrinology, 2020)
Osteoporosis is a metabolic skeletal disorder in which bone mass is depleted and bone structure is destroyed to the degree that bone becomes fragile and prone to fractures. Emerging evidence suggests that N6-methyladenosine (m6A) modification, a novel epitranscriptomic marker, has a significant role in bone development and metabolism. M6A modification not only participates in bone development, but also plays important roles as writers and erasers in the osteoporosis. M6A methyltransferase METTL3 and demethyltransferase FTO involves in the delicate process between adipogenesis differentiation and osteogenic differentiation, which is important for the pathological development of osteoporosis. Conditional knockdown of the METTL3 in bone marrow stem cells (BMSCs) could suppress PI3K-Akt signaling, limit the expression of bone formation-related genes (such as Runx2 and Osterix), restrain the expression of vascular endothelial growth factor (VEGF) and down-regulate the decreased translation efficiency of parathyroid hormone receptor-1 mRNA. Meanwhile, knockdown of the METTL3 significantly promoted the adipogenesis process and janus kinase 1 (JAK1) protein expression via an m6A-dependent way. Specifically, there was a negative correlation between METTL3 expression and porcine BMSCs adipogenesis. The evidence above suggested that the relationship between METTL3 expression and adipogenesis was inverse, and osteogenesis was positive, respectively. Similarly, FTO regulated for BMSCs fate determination during osteoporosis through the GDF11-FTO-PPARγ axis, prompting the shift of MSC lineage commitment to adipocyte and inhibiting bone formation during osteoporosis. In this systematic review, we summarize the most up-to-date evidence of m6A RNA modification in osteoporosis and highlight the potential role of m6A in prevention, treatment, and management of osteoporosis.